Pomoc finansowa podmiotów prywatnych udzielana jednostkom w stanach nadzwyczajnych - Czesak, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
In Financial Aid Provided by Private Persons to Entities during extraordinary measures, several forms of help )wire transfers, bank account deposits, charity text messages, crowdfunding) are discussed. In particular, the article is focused on public fundraising events governed under the Act on the Rules of Public Fundraising dated 14th of March 2014. The analysis also refers to the no longer binding Act on Public Fundraising Events dated 15th of March 1933. The discussion is related to the rules of public fundraising during the period of martial law and state of emergency due to natural disaster. The article presents new public fundraising rules, especially the fundraising entity’s obligation to report a fundraising event on the portal of public fundraising events.
Keywords: extraordinary measures; financial aid; public fundraiser; public fundraiser organizer; rules for conducting public fundraiser